2019
DOI: 10.1111/1440-1703.12029
|View full text |Cite
|
Sign up to set email alerts
|

Abundance of weeds and seeds but not of arthropods differs between arable habitats in an extensive Mediterranean farming system

Abstract: Agricultural intensification has profoundly affected European farmlands in the last decades, and their associated biodiversity has undergone a widespread decline. Although largely considered by farmers to be a threat to crop productivity, weeds and arthropods are key factors in farmland ecosystems and provide multiple ecosystem services. We analyze variations between three arable habitats—cereals, plowed and fallow fields—in the biomass of weeds, seeds and arthropods in an extensive rotation system of Central … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 67 publications
(121 reference statements)
0
6
0
Order By: Relevance
“…We acknowledge that estimating availability of food resources based mainly on potential effects of management practices is a simplification, which should be re-assessed with information from future studies. For example, accumulated effects of agricultural intensification over the years may result in the homogenization of specific food resources across land uses (Tarjuelo et al 2019). Regardless of this limitation, we showed that habitat suitability calculated with three simple variables (vegetation height, cover, and food abundance) allows for the production of habitat suitability indices that have biological meaning and explain variations in abundance of Little Bustards.…”
Section: Discussionmentioning
confidence: 83%
“…We acknowledge that estimating availability of food resources based mainly on potential effects of management practices is a simplification, which should be re-assessed with information from future studies. For example, accumulated effects of agricultural intensification over the years may result in the homogenization of specific food resources across land uses (Tarjuelo et al 2019). Regardless of this limitation, we showed that habitat suitability calculated with three simple variables (vegetation height, cover, and food abundance) allows for the production of habitat suitability indices that have biological meaning and explain variations in abundance of Little Bustards.…”
Section: Discussionmentioning
confidence: 83%
“…Pin-tailed sandgrouse and black-bellied sandgrouse are mainly granivorous species 20 , so they rely on the availability of seeds and seed banks. Seed availability is highly variable between habitats and among seasons, being also strongly influenced by agricultural intensification 18 , 50 . Within arable land, natural and semi-natural vegetation growing in grassy field boundaries and fallow land provides an important stock of seeds, being thus important habitat elements for these species 50 .…”
Section: Discussionmentioning
confidence: 99%
“…Biomass was calculated using the equations developed by Hódar (1996), which require the average length of each group. For this purpose, the length of 30 individuals per order was measured, except when the sample for a particular order was <30, in which case the mean was obtained from all the sampled individuals (see Tarjuelo et al., 2019 for similar procedures). Total and per‐order values were estimated.…”
Section: Methodsmentioning
confidence: 99%